The empirical analysis of technology and foreign direct investments - Corekcioglu, Selim (Studia Mundi – Economica, 2019)
The main aim of this study is to analyze the relationship between foreign direct investment and R&D spending using panel co-integration methods for upper middle-income economies and high-income economies. A larger level of investment is needed to increase the capital stock in order to ensure growth, but the typically low savings rate makes this difficult to achieve. Theoretically, it is expected that foreign direct investments would solve the saving inadequacy problem of the target country leading to economic growth by increasing capital accumulation. In this study, Levin Liu Chu and Pesaran Shin Unit Root tests, Pedroni panel co-integration tests was applied. According to the co-integration analysis, foreign direct investment and R&D spending move together in the long run. The results of the panel co-integration test which examines the long-term relationship, showed that R&D spending has stronger effect on foreign direct investment. In a globalized world, technology is one of the most important determinant of competition among countries. Technology improves profitability and competitiveness by increasing productivity. It can be seen that technological developments are coupled with economic growth throughout the history. With the involvement of technology transfers in production, added value will increase in manufacturing industry, so this will accelerate the process growth. Infrastructural investments, education system reforms tax reduction should be provided by government to promote technology level. The findings of this paper underline that capital accumulation and foreign direct investment are very important for countries in terms of development.